Endothelial fibrinolytic response onto an evolving matrix of fibrin. Issue 1 (December 2016) - Castillo, O.; Rojas, H.; Domínguez, Z.; Anglés-Cano, E.; Marchi, R.
Abstract Background Fibrin provides a temporary matrix at the site of vascular injury. The aims of the present work were (1) to follow fibrin formation and lysis onto the surface of human dermal microvascular endothelial cells (HMEC-1), and (2) to quantify the secretion of fibrinolytic components in the presence of fibrin. Methods Fibrin clots at different fibrinogen concentrations were formed on top of (model 1) or beneath (model 2) the endothelial cells. Fibrin formation or lysis onto the surface of HMEC-1 cells, was followed by turbidity. Clot structure was visualized by laser scanning confocal microscopy (LSCM). The secretion of uPA and PAI-1 by HMEC-1 cells was quantified by ELISA. Results The rate of fibrin formation increased approximately 1.5-fold at low fibrinogen content (0.5 and 1 mg/mL;p  < 0.05) compared to the condition without cells; however, it was decreased at 2 mg/mL fibrinogen (p  < 0.05) and no differences were found at higher fibrinogen concentrations (3 and 5 mg/mL). HMEC-1 retarded dissolution of clots formed onto their surface at 0.5 to 3 mg/mL fibrinogen (p  < 0.05). Secretion of uPA was 13 × 10−6 ng/mLper cell in the absence of RGD and 8 × 10−6 ng/mLper cell in the presence of RGD, when clots were formed on the top of HMEC-1. However, the opposite was found when cells were grown over fibrin: 6 × 10−6 ng/mLper cell without RGD vs. 17 × 10−6 ng/mLper cell with RGD. The secretion of PAI-1 by HMEC-1 cells was unrelated to the presence of fibrin or RGD, 7 × 10−6 μg/mLper cell and 5 × 10−6 μg/mLper cell, for the apical (model 1) and basal clots (model 2), respectively. Conclusions HMEC-1 cells influence fibrin formation and dissolution as a function of the fibrin content of clots. Clot degradation was accentuated at high fibrin concentrations. The secretion of fibrinolytic components by HMEC-1 cells seemed to be modulated by integrins that bind RGD ligands.